You are on page 1of 3

# cxcDirect Institute

## Completing the square

One general form of the quadratic expression is:
ax + bx + c
2

## Note that in all cases of the perfect square, 2 b if ( a = 1), then c = 2

()

the end term is the square of one-half the coefficient of the middle term.

## Perfect Squares: ( case a = 1)

Consider the Expression below where: ( a = 1, b = 6 and c = 9)
2

Incomplete squares
x 3

x + 6x + 9
9

First Term

## End ( last) Term Middle Term

The incomplete square can be viewed as a complete square with a portion removed. If we factorize this expression we get :
2 x + 6x + 9 =

( x + 3)

## Example1: What must be added to square:

x 4

x + 8x

to make it a perfect

which is called a complete ( or perfect ) square because it can be visualized as a square with each side = (x + 3)
(x + 3) x 3x (x + 3) (x + 3)2 x2 3x x 3 9 3

Solution: a = 1, b = 8 , c = ?

where

( x +3 )( x + 3 )

= =

c= 4
2

()
b 2

## Other examples of complete (perfect) squares are:

x + 4x + 4
x + 10x +25
2 2

(8 2)

= 16

= =

( x + 2) ( x + 5)

Giving

2 x + 8x + 16 =

( x +4)

.. perfect square

x + 12x +36 =

( x +6)

## cxcDirect Institute - 876 469-2775 Email: admin@cxcDirect.org website: www.cxcDirect.org

cxcDirect Institute -

Incomplete Squares contd In example1 , x 2+ 8x can be considered an incomplete square, where we showed that by adding 16, we could complete the square to create a perfect square). That is:
x +8x
2

## Functions of the form: ax 2+bx+ c

Any general Quadratic expression in the form ax 2+bx+ c can be converted to a new form a ( x + h )2+ k by first expressing h and k in terms of a, b and c. The formulas for h and k are determined as shown below. Finding h and k

+16

= ( x +4)2

eqn 2

## Now if we re-arrange eqn 2, we can see that:

2 x +8x = ( x + 4)

- 16
8 b (h= ) = 2 2

ax 2 + bx +c ... eqn 1
Step Action
Factor a from the first two terms of eqn.1 Complete the square of

= ( x + 4) 2 42 = ( x +h)2 h 2
where

=4

Result
b 2 a x + x +c a

1
This is an important conclusion which may be generalized as follows:

2
2 2 2 x +bx = ( x +h) h where

## the terms in bracket x (x +b a )

2

(x+

h=

b 2

b b ) ( ) 2a 2a

3
This is known as completing the square;
*****************************************************

## Place the result of step 2 back into step 1

a ( x+

b 2 b 2 ) ( ) +c 2a 2a

a(x+

## Example2: Express x 2+12x Solution: b = 12 , so

h= b =6 2
2 2

b ab ) 2+ c 2a 4a
2 2

in the form

( x +h) h

Simplify

b ab = a ( x + 2a ) + c 2 4a

2 2 b 4ac b = a( x+ ) +

2a

4a

x +12x = ( x +6) 6
2 2

= a ( x + h )2+ k

= ( x + 6) 36
h=

*****************************************************

## Example3 Express x 2 7x in the form now:

h=
2

b 2a 4ac b 4a
2

5
( x + h) h
2 2

Compare k=

7 2

= 3.5 Giving: h = = =
( x 3.5) 3.5
2 2 2

x 7x

b 2a

and

k=

4ac b 4a

( x 3.5) 12.25

## cxcDirect Institute - 876 469-2775

cxcDirect Institute -

Example 4 Express
2 2 x + 7x 13 in the form ( x + h) +k

## Example 7 Express Solution:

2x 7x +5
2

in the form

k a ( x + h )

( a = -2, b = - 7, c = 5)

b h= 2a

=
2

7 = 3.5 2
4 1(13 ) 7 41
2

h=

and

4ac b k= 4a
2

b 7 = 2a 4
4ac b 4a
2

= =

1.75
2

25.5

and

k=

42 5 (7 ) 4 2

= 11.125

so;

x +7x 13

= ( x +3.5)2 25.5
so:
2x 7x + 5
2

11.125 2 ( x +1.75 )

## Example 5: Express the function 1 5x x 2 Solution: in the form

k ( x + h )
2

Practice questions:
Express in the form:
a ( x +h ) + k 1. 2.
2x 6x + 1 x 7x 1 3x + 2x 7 1 5x + 2x 2 3x + x
2 2 2 2

## Express in the form:

k a ( x + h ) 6. 7. 8. 9. 10.
2

## Using the Formulas: ( a = -1, b = -5, c = 1)

h= b 5 = 2a 2
k= 4ac b 4a
2

x 2x + 3 2x + x + 6 3+ 2x 4x 1+ x x
2 2 2 2

= 2.5 =
=
4 1 1 (5) 41
2

3. 4.

and
so

= 7.25

5.

2 x 2x

1 5x x

7.25 ( x + 2.5)

# a 2 1 3 2 1 -1 -2 -4 -1 -2 h -1.5 -3.5 0.33 -1.25 -1.5 1 -0.25 -0.25 -0.5 0.25 k -3.5 -13.25 -7.33 -2.125 -0.25 4 6.125 3.25 1.25 2.125

## Functions of the form ax 2 + bx+ c

Example 6: Express

( a 1)

1 2 3 4 5 6 7 8 9 10

2 2 2 x 6x 13 in the form a ( x + h ) + k

Solution ( a = 2, b = - 6, c = -13)
h= b 6 = 2a 4
4ac b 4a
2

1.5
2

and

k=

4 2( 13 ) ( 6) 4 2
2

= 17.5

2 2 x 6x 13 = 2 ( x 1.5 ) 17.5

## Topic discussions in the math club (forum)

cxcDirect Institute - 876 469-2775